eLingua : Issue 1 : June 2018 / Academy of Language Studies - Mohd Amin, Noraziah; Razali, Wan Noorli; Mohamed, Sabariah; Chone, Liaw Shun; Ab Latif, Nur Afiqah; Ab. Rahim, Suzana; Desa, Melati; Zulkifli, Che Nooryohana; Marimuthu, Rasaya; Affendy Lee, NoorAzli; Yih, Mah Boon; Aboo Bakar, Rofiza (Academy of Language Studies, 2018)
1. “Jelajah Akademik” (Academic Tour) of APB UiTM Shah Alam to APB UiTM Penang 2. Internal Audit 2018 3. Congratulations, DM52 Promotion Recipients! 4. APB Language Editors for Faculty of Civil Engineering Vetting of Diploma Test Papers 5. Kursus Pra Persaraan 6. A meet-up with the rector and the top management 7. International Conference on Social Sciences, Education and Hu-manities (SOSEHUM) 2018 8. ENGLISH LANGUAGE CLUB PROGRAMMES 2018 9. Penglibatan staf APB dalani Misi Akademik 2018 10. Lemang dan Rendang di UiTM CPP! 11. A report on the Family Day Bowling Event 2018 12. APB Sports Women in KARISTA 2018 13. APB UiTMCPP Family Dav @ The Jerai Ilill Resort (11th-12th August 2018) 14. Q-Brainsters in the KIK Mini Convention UiTMCPP 2018 15. Language Carnival 2018 16. Language Colloquium 2017 17. Sebuah Kamus seribu makna—Siri 1 (SK Bandar Baru Perda, 1 Ogos 2018) 18. Projck Nur Ramadhan .APB 19. Barang-Barang Keperluan Asas di Free Market 2018 20.‘Getting to know you more’ 21. From the Third Languages 22. What Are You Thinking? 23. HIJAU 24. Rava Dulu vs Raya Sekarang